Performance Evaluation of Different Models of Cookstove to Improve Household Environment - Mehta, Manju; Sangwan, V; Sharma, D N (Journal of Agricultural Engineering, 2003)
Traditional cook stove used in the rural areas has many dangerous effects on the health of the users. To overcome this problem nine models of cook stove were developed by effecting modification in existing traditional mud cook stove. The performance of each cook stove was evaluated in terms of fuel burning rate, ash produced and charcoal produced. In first category, higher fuel-burning rate was observed in traditional cook stove M0 (1.97 kg/hr) followed by M1 (1.89kg/hr), M10 (1.73 kg/hr) and M9 (1.62 kg/ hr). The highest amount of heat was generated in model M1 (traditional cook stove with grate) and M10 (mud version of Priyagni cook stove). In the second category the highest amount of heat was generated in M0 (12010.63 kJ), followed by M4 (11223.04 kJ), M5 (10788.68 kJ), M3 (l0615.63kJ) and M2 (10526.97kJ). In the third category Model M8 required least amount of fuel i.e. 1.44kg/hr and provided only 0.085kg charcoal and 0.001kg of ash per kg of fuel used. There were differences in the quality of the smoke emitted by both the existing and improved cook stove in terms of suspended particulate matter, Sulfur dioxide and oxides of nitrates.